Pengaruh Penerapan Sistem Akuntansi Keuangan dan Efektivitas Pelaksanaan Pengawasan Anggaran Pada Kualitas Laporan Keuangan - Novi Paramartha, Ni Made Sarasita; Alit Suardana, Ketut (E-Jurnal Akuntansi; Vol 29 No 1 (2019), 2019)
The population in this study were all PNS Regional Financial Management Work Units (SKPKD) in the UPT. Disdikpora of Badung Regency. The sample collection technique used was purposive sampling method. Respondents in this study were the Head of the UPT, the subdivision of finance and 3 staff of the finance department of the UPT Disdikpora in Badung Regency totaling 6 UPT spread across all sub-districts, so the number of samples set was 30 people. Methods of collecting data using questionnaires. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that the local government financial accounting system has a positive effect on the quality of financial statements and the effectiveness of the implementation of budget monitoring has a positive effect on the quality of financial statements. Keywords : Financial accounting system; budget supervision; report quality.